Assessment of Cytogenotoxicity of Plastic Industrial Effluent Using Allium cepa Root Tip Cells - Mohammed, Jibril Sani; Mustapha, Yahaya; Him, Madu Abdulkarim; Danladi, Zandam Nuhu (International Journal of Cell Biology, 2023)
The effects of plastic effluent in Kano Metropolis on cytotoxicity and genotoxicity were examined using a test on Allium cepa root cells. The physicochemical characteristics of industrial wastewater were assessed, and the results showed values that were higher than the required criteria; this implies that the effluent was not treated before to disposal. For 96 hours, a group of 40 onion bulbs was cultivated in various concentrations of plastic effluent: 15, 30, 45, and 60% (v/v). The control was made up of distilled water. Following 96 hours, the four treated root tips from each replication’s bulbs were harvested and subjected to the acetoorcein squash technique for cytogenetic analysis. High concentrations of the industrial effluents had severe development retarding effects on the root tips. Root growth was inhibited with EC50 values of 48% after treatment with the effluents in comparison to control. When Allium cepa was exposed to different quantities of plastic effluent, the results of an analysis of variance (ANOVA) showed that the mean root length varied, and this variation was statistically significant (p<0.05). With rising effluent concentrations, the mitotic index (M.I.) rapidly dropped. Chromosomal abnormalities were caused by the plastic effluent in the root cells of Allium cepa, especially sticky chromosome and binucleated cells being the most frequently seen at lower concentrations of 15%. It was discovered that the compounds found in plastic wastewater could injure live beings as well as harm the environment if not treated. Legal mechanisms must be used to push businesses and manufacturers to switch to environmentally friendly technologies.